2015
DOI: 10.4103/0019-5545.171842
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on psycho-socio-demographic and clinical profile of patients with bipolar versus unipolar depression

Abstract: Background:Several studies have revealed significant differences between bipolar (BP) and unipolar depression (UP). Misdiagnosing BP depression results in suboptimal symptom resolution, induction of manic switch, mixed state, or accelerated cycling. This study compares various psycho-socio-demographic, longitudinal course, and phenomenological factors associated with BP and UP depression.Materials and Methods:We compared 30 UP and 30 BP depression patients using a specially designed intake proforma, Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 14 publications
5
24
0
Order By: Relevance
“…These findings support established theories that specify shared cross‐diagnostic mechanisms in the development of delusional thinking . Additional studies confirmed that grandiosity reaching delusional severity was most frequently reported by individuals with manic presentations, whereas persecution and paranoid delusions were most frequently reported in studies examining depressive episodes and general samples of individuals with BD irrespective of current mood episode . These results suggest a potentially direct effect of mood on the content of delusions, such that particular delusional themes may be associated with certain mood states .…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…These findings support established theories that specify shared cross‐diagnostic mechanisms in the development of delusional thinking . Additional studies confirmed that grandiosity reaching delusional severity was most frequently reported by individuals with manic presentations, whereas persecution and paranoid delusions were most frequently reported in studies examining depressive episodes and general samples of individuals with BD irrespective of current mood episode . These results suggest a potentially direct effect of mood on the content of delusions, such that particular delusional themes may be associated with certain mood states .…”
Section: Resultssupporting
confidence: 81%
“…Higher AH rates in mania were confirmed in these studies, but the differences reported were actually quite modest. Further examination of AH phenomena may therefore be required within the depressive phases of BD …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparatively more unipolar cases were female and bipolar were male, which is in concordance with few other clinic-based studies but contradictory to many other studies which were basically population based. [18][19][20][21][22] Majority of the cases were of the productive age group, which might had led to a tremendous loss for the societal development.…”
Section: Discussionmentioning
confidence: 99%